Active closed‐loop gate voltage control method to mitigate metal‐oxide semiconductor field‐effect transistor turn‐off voltage overshoot and ring. Issue 8 (1st September 2013) - Wang, Xiaowei; Sun, Yue; Li, Tiecai; Shi, Jian
Abstract : Voltage overshoot and ring will occur during metal‐oxide semiconductor field‐effect transistor (MOSFET) turn‐off, when it is embedded in circuits with inductive load and operates in pulse width modulation mode. The voltage overshoot and ring not only increase the system voltage stress, but also produce radiated and conducted electromagnetic interference. Based on the analysis of the influence of the gate voltage on the MOSFET turn‐off behaviour, this study presents an active closed‐loop gate voltage control method to mitigate the voltage overshoot and ring. The proposed method senses the instant when the MOSFET drain current starts to fall by comparing the drain voltage with the bus voltage. Once the instant has been detected, a turn‐off assistance voltage with proper amplitude and adjustable duration is generated and applied to the gate to mitigate the overshoot and ring. The delay of the gate control loop, including the delay of the comparator, can be compensated by proper choice of the components. Both simulations and experiments results indicate that the MOSFET turn‐off voltage overshoot is largely reduced and the ring is almost completely eliminated. At the same time, the turn‐off loss and EMI are also minimised.